(3JSjjQ GdehGQO GdHTQjIs (3OQGSI MGdGJs - (3YOeGf(B, (3eQjRbs ((3GdLRGFQs (3LShQs, 2019)
(3jTed gPG GdcJGH OQGSGJ ddMGdGJ GdNGUI HhXjaI JSjjQ GdehGQO GdHTQjI chXjaI ebGQfI HGdhXGFa GdCNQi Ydi eSJhi GdeDSSI JdJgG OQGSGJ MGdI GdhUa GdhXjaj, JNWjW GdehGQO GdHTQjI, GdGNJjGQ hGdJYjjf,GdJQbjI, GdCLhQ, OhQGf GdYed, GdJZjH, GdCeGf GdhXjaj, GdJbjje hZjQgG(B.s
Keywords: (3EOGQI GdCaQGOs; (3GdEOGQI GdYGeIs